The Role of Motivation and Organizational Behavior in Managerial Decision-Making: Rationality or Behavioral Influence? A Behavioral Accounting Perspective - Lovanka Salsabila Aulia Putri; Nadira Ramadhani; Muhammad Farhan; Emylia Yuniarti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Managerial decisions in accounting practice often deviate from the assumptions of pure rationality due to the influence of psychological and organizational factors. In practice, managers do not always make decisions solely based on logical calculations and financial information, but are also affected by motivation, cognitive biases, emotions, organizational culture, reward systems, and social pressures within the workplace. This study aims to analyze the role of motivation and organizational behavior in managerial decision-making from a behavioral accounting perspective, particularly in explaining the tension between rationality and behavioral influence in organizational settings. The research employs a Systematic Literature Review (SLR) method using the PRISMA framework by qualitatively reviewing accredited articles indexed in Scopus, SINTA, and Google Scholar from 2020–2026. The findings indicate that managerial decision-making is strongly influenced by intrinsic and extrinsic motivation, bounded rationality, emotional conditions, and organizational dynamics such as corporate culture, leadership patterns, and team interactions. These behavioral factors significantly shape how accounting information is interpreted and used in decision-making processes. The study concludes that behavioral accounting provides a more comprehensive framework for understanding managerial decisions by integrating psychological and organizational dimensions into accounting practices and professional judgment, particularly in increasingly dynamic, uncertain, and technology-driven modern organizational and business environments across various industrial sectors.